Role of Spinal Cord Akt-mTOR Signaling Pathways in Postoperative Hyperalgesia Induced by Plantar Incision in Mice - Xu, Bing; Liu, Su-Su; Wei, Jin; Jiao, Zi-Yin; Mo, Cheng; Lv, Cheng-Mei; Huang, Ai-Lan; Chen, Qi-Bo; Ma, Li; Guan, Xue-Hai (Frontiers in Neuroscience, 2020)
Poor postoperative pain (POP) control increases perioperative morbidity, prolongs hospitalization days, and causes chronic pain. However, due to the specific mechanisms leading to POP is unclear, the identification of optimal perioperative treatment remains elusive. The etiology of POP may be different from antigen-induced inflammatory pain and neuropathic pain. Akt and mammalian target of rapamycin are expressed in the spinal cord, dorsal root ganglion, and sensory axons. In this study, we explored the role of Akt and mTOR in the pain-related behaviors induced by plantar incision in mice. The plantar incision activated the spinal Akt and mTOR in a dose dependent manner. Pre-treatment with Akt inhibitors prevented the activation of mTOR dose-dependently. In addition, the blocking of the Akt-mTOR signaling axis attenuated the pain-related behaviors and the spinal Fos protein expression induced by plantar incision. Our observations demonstrated that Akt-mTOR might be a potential therapeutic target for treatment of POP.